Colesevelam for Type 2 diabetes mellitus: an abridged Cochrane review - Ooi, Cheow Peng; Loke, Seng Cheong (Wiley-Blackwell Publishing, 2014)
Aim Colesevelam, a second-generation bile acid sequestrant, may be beneﬁcial in controlling both glycaemia and lipids simultaneously. Our goal was to evaluate the systemic effects of colesevelam on Type 2 diabetes mellitus. Method The original Cochrane review was conducted using the methodology for the systematic review of interventions of the Cochrane Collaboration in RevMan 5.2. We comprehensively searched the literature in several databases up to January 2012. Two reviewing authors independently selected and extracted the data, and then evaluated the quality of the randomized controlled trials that met the inclusion criteria. Results Six randomized controlled trials were selected, which ranged from 8 to 26 weeks in duration. A total of 1450 participants were divided into two groups: those treated with colesevelam and no other anti-diabetic drug treatments/ placebo, or with colesevelam added on to anti-diabetic drug treatments. The colesevelam added on to anti-diabetic agents demonstrated a statistically signiﬁcant reduction in the fasting blood glucose (mean difference of –0.82 mmol/l, 95% CI –1.2 to –0.44), HbA1c (mean difference –0.5%, 95% CI –0.6 to –0.4) and LDL cholesterol (mean difference – 0.34 mmol/l, 95% CI –0.44 to –0.23). There were no reported data on weight. Non-severe hypoglycaemic episodes were infrequently observed. Conclusion The limited number of studies concerning the treatment with colesevelam added to anti-diabetic agents showed signiﬁcant effects on glycaemic control; however, more research on the reduction of cardiovascular risks is required. Furthermore, long-term data on the health-related quality of life and all-cause mortality also need to be investigated.